2022
DOI: 10.1093/cvr/cvac099
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the genetic causes of bicuspid aortic valve disease

Abstract: Aims The present study aims to characterise the genetic risk architecture of bicuspid aortic valve (BAV) disease, the most common congenital heart defect. Methods and results We carried out a genome-wide association study (GWAS) including 2,236 BAV patients and 11,604 controls. This led to the identification of a new risk locus for BAV on chromosome 3q29. The single nucleotide polymorphism (SNP) rs2550262 was genome-wide sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In this study, we identified heterozygous HOXA1 dominant negative mutations in humans with BAV. Several studies showed that BAV is a polygenic disorder 4,24 , so we cannot exclude that HOXA1 variants act in concert with other genetic factors to contribute to the onset of the BAV phenotype. Using in vivo experiments, we demonstrated that homozygous Hoxa1knock-out and Hoxa1 −1His knock-in mice present BAV, and that targeting the zebrafish hoxa1a ortholog resulted in aortic valve defects that could be rescued by expressing the wild-type human HOXA1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, we identified heterozygous HOXA1 dominant negative mutations in humans with BAV. Several studies showed that BAV is a polygenic disorder 4,24 , so we cannot exclude that HOXA1 variants act in concert with other genetic factors to contribute to the onset of the BAV phenotype. Using in vivo experiments, we demonstrated that homozygous Hoxa1knock-out and Hoxa1 −1His knock-in mice present BAV, and that targeting the zebrafish hoxa1a ortholog resulted in aortic valve defects that could be rescued by expressing the wild-type human HOXA1.…”
Section: Discussionmentioning
confidence: 94%
“…To further examine if variants in genes associated with BAV (e.g. NOTCH1, GATA4, GATA5, MUC4, and ROBO4) and implicated in valvular and aortic defects were present in individuals carrying deletion or insertion in the poly-histidine tract of HOXA1, we performed exome sequencing 16,17,19,24 . After exome sequencing analysis no relevant variants were identified except for three missense variants in NOTCH1 and GATA5 genes.…”
Section: Identification Of Indel Variants In the Poly-histidine Tract...mentioning
confidence: 99%
“…Interestingly, the duplication CNV associated with BAV in TS is also associated with conotruncal defects and left-sided lesions in 22q11.2 deletion syndrome suggesting that genetic modifiers of CHD may manifest differently on different high-risk backgrounds (Prakash et al 2016 ). CRELD1 has not been implicated in the pathogenesis of non-syndromic, non-familial BAV via GWAS (Helgadottir et al 2018 ; Fulmer et al 2019 ; Bjornsson et al 2018 ; Yang et al 2017 ; Gehlen et al 2022 ; Gago-Díaz et al 2017 ). Thus, the effect of CRELD1 variants may be more penetrant in the setting of Xchr haploinsufficiency, representing an as-of-yet unidentified mechanism contributing to the polygenic heritability of BAV.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic basis of CAVD is complex, as exemplified by the gene-phenotype linkage of BAV, a congenital valve abnormality with strikingly variable genetic etiologies, ranging from intricate inheritance patterns to sporadic cases. Beyond certain syndromes and congenital malformations involving the left ventricular outflow tract, the heritability of BAV appears to be largely polygenic, 13 with an up to 10-fold increased prevalence in first-degree relatives as compared to the general population. In a recent GWAS involving 466 BAV cases and 4660 controls, a noncoding variant near GATA4 (rs6601627) reached genome-wide significance with a protein-altering variant in this cardiac-specific transcription factor (rs3729856) showing near-significant association.…”
Section: (Epi-)genome: a Crucial Determinant Of Aortic Valve Calcific...mentioning
confidence: 99%